Towards a sustainable campus -the impact of detailed physical components on the sustainable mental image. University of Mosul as a case study - Hazim, Dhuha; Ismaeel, Emad (Al-Qadisiyah journal for engineering science, 2025)
The urban milieu of a campus comprises a intricate constitution of interconnected elements that collectively shape a complex ‎environment. The interrelationships among these elements play a pivotal role in the design of an efficient and sustainable urban ‎framework. This study aims to elucidate the impact of specific physical factors on the visual sustainability of the urban fabric. The ‎University of Mosul campus serves as the case study for this investigation. The research identifies and categorizes the components ‎that influence the mental image of the campus, encompassing both built and unbuilt elements. The methodology employed ‎integrates qualitative and quantitative approaches, utilizing a questionnaire and computer software to analyze the visual properties ‎of the influencing factors. The findings of the study reveal that these characteristics and relationships contribute differentially to the ‎formation of a sustainable urban image, with several factors being instrumental in enhancing and developing the visual sustainability ‎of campus environments, both presently and in the future.‎